The female body as a site of embodying personal and cultural memories in Nawal El-Saadawi’s autobiographies (Western African Literary and Cultural Studies, 2021)
Although the concept re/making the body is often conceived as denoting re-constructions of the material body, this paper expands this notion to include issues of embodiment. It analyses how the female body might serve as a textual strategy used to represent the embodiment of female trauma in autobiography. The paper therefore deconstructs and extends the boundaries of conceptions of re-making the body from previous pre-occupation with the physical body to include social constructions of the body. The focus is on two autobiographies by Nawal El Saadawi: A daughter of Isis (1999) and Walking through fire (2002). The paper highlights the theme of female body memory because trends in representations of gendered bodies in public discourses imagine the male as the mind and the female as a body to be defined and determined.